SOCIAL GAMES (Fiep Bulletin - online, 2016)
Among the activities to be performed by the Physical Education are appointed games, easy to understand actions, which have different functions: both can serve for the movement of the body in order to give greater flexibility to those who are participating, how much, and is That's what matters in this study, may help the individual to interrelate with his neighbor, allowing you thus socialization in these actions. The game is a spontaneous and selfless activity, assuming a freely chosen rule that must be observed, or deliberately set obstacle that must be overcome. For a child, it is essential to learn the grammar rules so that it can participate in society also makes up creating personal skills and consolidate the body image so that it can be integrated into a group. To this end, the need for physical education classes and activities of social function.
Keywords: Physical Education; Social Game; Socialization.